Revitalizing Linguistic Learning Through Digital Technology In The Era Of Society 5.0 - Hidayatullah, Naufal; Nirwana, Andri; Rhain, Ainur (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The purpose of this article is to describe how these models are applied in learning activities and to examine learning models deemed successful in revitalizing linguistics education using digital technology in the era of Society 5.0. This study employed a literature review methodology, which included a review of various relevant scientific sources, including books, academic journals, scientific articles, and previous research findings. The research findings revealed that several learning models, including blended learning, problem-based learning, project-based learning, collaborative learning, and AI-based learning, have been proven to improve the quality of linguistics learning when combined with various digital technology platforms, such as Google Classroom, LMS, Zoom, Padlet, ChatGPT, Grammarly, and Duolingo. The implementation of these models provides a more flexible, interactive, and collaborative learning experience tailored to students' needs. Furthermore, the use of digital technology also contributes significantly to developing critical thinking, creativity, and communication skills in students. Therefore, the revitalization of linguistics learning based on digital technology is considered highly relevant and strategic as a foundation for developing innovative learning in the era of Society 5.0.